AGAMA DAN PROBLEM SOSIAL EKONOMI: TELAAH TEOLOGI KEBANGSAAN ATAS GAGASAN REVOLUSI MENTAL UNTUK PERUBAHAN PEMBANGUNAN YANG BERKEADILAN - salamudin salam (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Abstract This article aims to explain how religion as a living entity in the society is connected to socio-economic issues. Religion contains the noble values ??of social life. These values ??are then interpreted by religious figures as the conduits for translating religious valuesinto practical application, to be contextualized and implemented in everyday life. The concept of ??mental revolution launched by President Joko Widodo finds a point of intersection with religious moral-ethical messages facilitating the movements for social change and addressing society's socio-economic challenges. The important point is how religious values ??are able to answer the problems of the people.The solution is to restore the role of religious values ??and figures in the mental revolution movement for equitable development,employing various movement strategies, both structural and cultural.